Begabungsförderung für Alle!? Bausteine potenzialorientierten und begabungsförderlichen Biologieunterrichts für heterogene Lerngruppen (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
In line with a multidimensional and dynamic understanding of giftedness, which assumes that the promotion of giftedness is talent development, teaching must be designed in such a way that all students are enabled to develop their potential and talents. In cooperation between science education and school practice, elements for potential- and talent-oriented biology education have been developed. In this article, the different elements are theoretically located and concrete examples are presented.
Keywords: Potential orientation; talent development; growth-oriented attitude; research-based learning; school- and lesson development; science-practice transfer